Many Transcription Factors Contribute to C. elegans Growth and Fat Storage - Mori, Akihiro (Genes Cells, 2017)
Reverse genetic screens by RNA interference (RNAi) in model organisms such as the nematode Caenorhabditis elegans have provided numerous insights into gene function, thereby connecting genotype to phenotype. However, genes that contribute only subtly are often missed because relatively large numbers of measurements and reliable quantification are required to overcome experimental and biological noise that may mask subtle phenotypic effects. Here, we address this challenge by focusing on two phenotypes in C. elegans: growth and fat storage. We performed comprehensive RNAi knockdown of transcription factors (TFs), as these are known important regulators of biological processes during development and the maintenance of homeostasis. Microscopy images of TF knockdown animals stained with Oil-red-O (ORO) were captured and body size (proxy for growth) and ORO staining intensity (proxy for fat storage) were precisely quantified using a newly developed imaging tool we named IPPOME (Image Processing for Precise and Objective MEasurement). We found that a surprisingly large proportion of TFs contribute to growth and fat storage, but that most TFs have only subtle, yet significant effects. This study provides a blueprint for studies of other genes and phenotypes in C. elegans.